The political situation in Thailand and the abdication of King Prajadhipok from the throne (1933-1935) - Hatem, Assistant Prof.Maher Chasib; Hussein, Athraa Saad (Thi Qar Arts Journal, 2023)
This research deals with the topic (the political situation in Thailand and the abdication of King Praja Depok from the throne 1933 1935), after the occurrence of the constitutional revolution in June 1932, which achieved radical changes in the structure of the political, economic and social system in Thailand, and the rule in it became from an absolute monarchy to A constitutional system, in addition to the fact that King Prajadipok became the first constitutional monarch to rule the Kingdom of Thailand, but it was the beginning of many differences and political conflicts between the king and the princes on the one hand and the new constitutional government on the other hand, as it caused many coups, the first of which was in 1933 by the president Ministers Mattu Pakorm, on the National Assembly, and the other led by Prince Poweradet, King Prajadipuk was forced to leave Thailand for his self-imposed exile in Europe, and from there he began bargaining with the Thai government to accept all his conditions, threatening to abdicate the throne if he did not These conditions are implemented , in return , the government rejected all his conditions, which  made him  save his threat , knowing that the political differences and conflicts at that  time  were  not limited  to the person of the king ,Bar Jadebok , and the government, the constitution. In Thailand, it even included members of the ruling People's Party among themselves from the civilian wing and its military counterpart, as it became competing with each other, so after getting rid of the king, each of them began working to overthrow the other through a secret struggle, in addition to some of them claiming that the government became unique. With its political decisions and ruling a dictatorial rule through one party, the People's Party, asking it to allow it to organize new political parties in the country, so that it can participate in the next elections to be held in 1933.